ANALISIS IMPLEMENTASI KEARIFAN LOKAL MELALUI PENDEKATAN EKOFEMINISME SEBAGAI UPAYA ADAPTASI DAMPAK PERUBAHAN IKLIM PADA WANITA DAYAK BIDAYUH DI PERBATASAN - Benedhikta Kikky Vuspitasari; Usman Usman (POLITEKNIK LP3I JAKARTA, 2025)
This study emphasizes the strategic role of the Dayak Bidayuh community, especially women, in facing the challenges of climate change by using an approach based on local wisdom and culture. Methods such as shifting cultivation systems, preservation of local seeds, customary prohibitions, and agrarian rituals indicate that this community has a long-standing ecological adaptation system. Women are the main actors in community ecofeminist practices because they play an important role in environmental conservation, cultural tradition inheritance, and local food production. However, the effects of climate change such as seasonal uncertainty, natural resource destruction, and loss of spiritual practices threaten the traditional role and resilience of the community. It is evident that adaptation approaches driven by cultural values, such as strengthening women's creative economy, preserving customary forest areas, and integrating traditional knowledge with climate technology, are inclusive. These strategies are in line with the principles of Gender Equality and Social Inclusion (GESI). The local wisdom of the Dayak Bidayuh can serve as a model for community-based, inclusive, and sustainable climate adaptation, if women are recognized as guardians of ecology and culture and are actively involved in climate adaptation programs, education, and local resource-based economic development